2011
DOI: 10.1139/z10-102
|View full text |Cite
|
Sign up to set email alerts
|

Long-term feeding ecology of Great Black-backed Gulls (Larus marinus) in the northwest Atlantic: 110 years of feather isotope data

Abstract: Recent changes to the ecology of the northwest Atlantic are affecting feeding relationships at many trophic levels. With declining fish stocks and fewer fisheries discards, generalist birds such as Great Black-backed Gulls ( Larus marinus L., 1758) may shift their diets. To test whether such a change has occurred, we measured stable nitrogen and carbon isotope ratios of flight feathers collected from modern and museum-preserved birds (1896–2006). We then compared trends in isotope ratios with trends in regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 59 publications
0
22
2
1
Order By: Relevance
“…This contrasts with other seabirds over similar time frames in the North Atlantic [38,51], North Pacific [18,52], and Indian and southern Oceans [53][54][55]. While we found that ivory gull stable-isotope values remained constant, their diet could have changed to different prey with similar isotopic values.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This contrasts with other seabirds over similar time frames in the North Atlantic [38,51], North Pacific [18,52], and Indian and southern Oceans [53][54][55]. While we found that ivory gull stable-isotope values remained constant, their diet could have changed to different prey with similar isotopic values.…”
Section: Discussioncontrasting
confidence: 90%
“…We used values of -0.007‰ for b his , the historical global annual decline in d 13 C [36], as no region-specific measurements are available, and -0.026‰ for b mod , the change in oceanic d 13 C in the North Atlantic measured from 1950 to 1993 [37], following the same rationale as Farmer & Leonard [38].…”
Section: (B) Laboratory Analyses (I) Stable Isotopesmentioning
confidence: 99%
“…Based on an estimated increase of 3‰ with each trophic level (33), our δ 15 N data translate to a decline of one-half, fourfifths, and two-thirds of a trophic level for the populations on Maui, Lanai, and Hawaii, respectively. Studies of freshwater and near-shore marine ecosystems show that similar trophic declines in generalist seabirds are associated with fishing pressure and declines in prey abundance (34)(35)(36). Consistent with this trend, δ 15 N decline in the Hawaiian petrel was coincident with the onset of large-scale, industrial fishing in the oceanic Pacific, which could have affected petrel diet through several mechanisms.…”
mentioning
confidence: 72%
“…While initially applied to bone collagen to identify shifts in prehistoric human diets (Ambrose, 1986), this technique has also been applied to animal bones and keratinized tissues to explore changes in marine and terrestrial food webs (Thompson et al, 1995;Farmer and Leonard, 2011;Crowley et al, 2012;Wiley et al, 2013;Moreno et al, 2016) and linkages between them (Darimont and Reimchen, 2002;Chamberlain et al, 2005;Blight et al, 2015;Matsubayashi et al, 2015). Shifts in diet between types of mammal carrion (marine, terrestrial herbivores, and grainfed livestock) by California Condors (Gymnogyps californianus; Chamberlain et al, 2005) and from vertebrate herbivores and toward plant materials by Brown Bears (Ursus arctos; Matsubayashi et al, 2015) have been detected by comparing both the δ 15 N and δ 13 C values of museum specimen tissues from the predators and potential prey types during different time periods.…”
Section: Introductionmentioning
confidence: 99%